Assessment of Sex Hormones and Gonadotropins levels in Alzheimer Patients: - Karimi, Fariba; Borhani Haghighi, Afshin; Petramfar, Payman; Afreidoon, Arnoosh (Galen Medical Journal, 2015)
Backgrounds: Increasing age is the most significant risk factor for Alzheimerʾs disease and depletion of sex hormones is an important consequence of normal aging. This study aimed to investigate the serum level of sex hormones and gonadotropins in patients with Alzheimerʾs disease in comparison with the control group. Materials and Methods: This case-control study was conducted between October 2010 and November 2011 in Shiraz Mottahari Clinic. Fifty-one patients with Alzheimer’s disease and 49 age-matched volunteers without dementia participated in this survey. Both groups were evaluated by two neurologists according to DSM- IV criteria. Blood samples were taken after 12 hours fasting to measure serum levels of estradiol, testosterone, gonadotropins and sex hormone binding globulin (SHBG). Results: Eighteen females and 33 males in the patient group, and 23 females and 26 males in the control group participated. There were no significant differences between the two groups regarding their gonadotropins, estradiol, free androgen index and body mass index, but the mean level of SHBG in patients was significantly higher than the control group (P=0.03). In addition, male patients had a higher total testosterone mean compared to male subjects in the control group (P=0.02). Conclusion: Our findings regarding testosterone levels in males of two groups were contrary to some of the previous surveys in this area. Moreover, we found higher levels of SHBG in patients compared to the control subjects. Further investigation is needed to define whether and how changes of sex hormones can affect brain health and vulnerability to Alzheimer’s disease.[GMJ.2015;4(4):139-45]